Have a son, gain a voice: Son preference and female participation in household decision making - Rashid Javed; Mazhar Mughal (Université de Pau et des Pays de l'Adour, 2018)
Son preference is common in many Asian countries. Though a growing body of literature examines the drivers and socioeconomic impacts of phenomenon in case of China and India, work on other Asian countries is scarce. This study uses nationally representative survey of over 13 thousand households from Pakistan (PDHS 2012-13) to analyze the effects of observed preference for sons on women's participation in intra-household decision-making. Four key intra-household decisions are considered: decisions regarding healthcare, family visits, large household purchases and spending husband's income. These correspond to four categories of household decisions, namely healthcare, social, consumption and financial. Probit and Ordered Probit are employed as the main estimation techniques and other determinants of household decision-making are controlled for. Besides, a number of matching routines are employed to account for the possibility of potential selection bias. We find that women with at least one son have more say in household decisions. Bearing at least one son is associated with 5%, 7% and 5% higher say in decisions involving healthcare, social and consumption matters respectively. Women's role in financial affairs, however, does not differ significantly from women with no sons. Female participation in decision-making grows significantly with the number of sons but only up to the third parity. These results are particularly visible among younger, wealthier and educated women, and those who got married earlier. The findings suggest a limited improvement in women's bargaining power at home resulting from the birth of one or more sons. This in part explains higher desire for sons expressed by women compared to men in household surveys. – – La préférence pour les garçons est courante en asie. Alors que beaucoup d'études s'intéressent aux facteurs et aux impacts socioéconomiques de ce phénomène en Chine et en Inde, les travaux sur les autres pays asiatiques sont plus rares. A partir d'une enquête nationale réalisée sur plus de 13 000 ménages pakistanais (PDHS 2012-13), cette étude analyse les effets de la préférence pour les garçons sur la participation des femmes aux décisions prises dans le ménage. Quatre décisions importantes du ménage seront prises en compte : celles relatives aux soins de santé, aux visites de famille, sur les achats du ménage et sur l'affectation des dépenses des revenus du mari. Celles-ci représentent quatre catégories des décisions au sain du ménage : les décisions lié à la santé, aux liens sociaux, à la consommation et aux affaires financières. Les méthodes Probit et Probit Ordinal sont utilisées pour les estimations de base et d'autres déterminants liés aux décisions prises dans le ménage seront pris en compte. De plus, méthodes d'appariment sont utilisées pour tenir compte d'éventuels biais de sélection. Les résultats indiquent que le fait d'avoir au moins un fils a une influence sur les décisions du ménage. Le fait d'avoir au moins un fils est associé à une hausse de 5%, 7% et 5% sur les décisions impliquant respectivement les soins de santé, les relations sociales et la consommation. L'implication des femmes dans les finances du ménage ne varie pourtant pas significativement avec celle des femmes sans fils. La participation des femmes dans les prises de décision augmente avec le nombre de fils mais seulement jusqu'à 3 garçons. Ce résultat entraine une amélioration relative sur le pouvoir de négociation des femmes au sein du ménage suite à la naissance d'un ou plusieurs garçons. Cela explique en partie le désir plus fort des femmes d'avoir des fils par rapport aux hommes, selon les enquêtes ménages.
Keywords: D13; J13; C13; C70; 330; Son preference; Gender bias; Sex selection; Female decision-making; intrahousehold bargaining; Pakistan